2014
DOI: 10.1016/j.ihj.2014.10.416
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death early after ST elevation myocardial infarction with and without severe left ventricular dysfunction

Abstract: The incidence of SCD is high in first month after STEMI, irrespective of LV function. The number of SCD is higher in Group B patients. Algorithms to assess risk of SCD in early post STEMI period are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In patients post MI, 16 studies were identified involving a total of 250766 patients[24-39](Table 3). The absolute risk of SCD in these studies varied from around 4.9%-8%[24,26,30,33]. The absolute risk of SCD was 4.9% in the first month post-MI and decreased thereafter[24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients post MI, 16 studies were identified involving a total of 250766 patients[24-39](Table 3). The absolute risk of SCD in these studies varied from around 4.9%-8%[24,26,30,33]. The absolute risk of SCD was 4.9% in the first month post-MI and decreased thereafter[24].…”
Section: Resultsmentioning
confidence: 99%
“…One study showed a risk of SCD of 7% at 30 d and 11% at 2 years[30]. Another study showed a risk of SCD at 4% in those with EF > 35% and 8% in those with EF < 35% at one year[33].…”
Section: Resultsmentioning
confidence: 99%
“…There is limited data on incidence of sudden death after an MI in India [ 8 ]. Patients suffering an MI in India are different from those in the West, principally being younger and with a higher prevalence of diabetes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%